Legal Analysis of the Detention of Suspects of Theft Crimes by Investigators at the Sagulung Police Sector, Batam City - Deni, Rindu Rizki Permata; Tri Bawono, Bambang (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Criminal procedure law is a law that regulates how to maintain and defend material criminal law and regulates how to try cases in criminal courts by criminal judges. The Criminal Procedure Code regulates the main points, the principles in Indonesian criminal procedure law, namely: the principle of legality, the principle of opportunity, the principle of equal treatment before the law, the principle of presumption of innocence, the principle of arrest, detention, search, and confiscation are carried out based on written orders from authorized officials, the principle of compensation and rehabilitation, the principle of fast, simple and low-cost trials, the principle that suspects or defendants have the right to receive legal assistance, the principle that the court examines criminal cases with the presence of the defendant, the principle of open trials to the public, the principle of accusatoir (placement of suspects as subjects). Law Number 2 of 2002 concerning the Republic of Indonesia Police, in Articles 13 and 14 outlines the functions and roles of the Police, namely: Article 14 (1) letter g makes the substance of the details of the Police's duties in the field of criminal investigation and inquiry in accordance with the Criminal Procedure Code and other laws and regulations, which relate to the duties and authority of the Police in the law enforcement process. The Criminal Procedure Code gives the main role to the Police to carry out the task of investigating and investigating criminal acts (in general) without limits within the scope of the law, so that basically the Police are given the authority by the Criminal Procedure Code to conduct investigations and investigations of criminal acts.